Process integration in an iron ore upgrading process system : analysis of mass and energy flows within a straight grate induration furnace - Nordgren, Samuel; Dahl, Jan; Wang, Chuan; Lindblom, Bo (Luleå tekniska universitet, Energivetenskap, 2008)
This paper is a part of a project which aim is to develop a process integration model for the Swedish iron ore company LKAB's production system in Malmberget. Within the facility, there are two pelletising plants which were started up 1973 and 2006, respectively. Both pelletising plants are using the straight grate induration furnace, and they are the most energy intense process units within the facility. Basically a straight grate induration furnace consists of three different zones, i.e. a drying zone, a firing zone and a cooling zone, and their purpose is to upgrade crude iron ore to the final product of iron ore pellet. As an initial step of the project, the mass and energy flows within a straight grate induration furnace have been analysed. The outcome of the analysis will in the future constitute as a basis towards a total mass and energy balance for the whole production chain within the facility in Malmberget. Later on the model will be used to optimize, primarily, energy consumption and environmental impact. Godkänd; 2008; 20080917 (samnor)